LINE × TESTER ANALYSIS OF PHYSIOLOGICAL TRAITS FOR FRUIT YIELD AND RELATED CHARACTERS IN LUFFA ACUTANGULA (ROXB.) L. - SHIVANAND B. KOPPAD; UKESH L. CHAVAN A; EKHA HALLUR (The Bioscan, 2015)
The present study was carried out to know the influence of physiological traits on the total fruit yield per vine in Luffa acutangula during 2012 -2014. The genotype L4 and T4 were found to be good general combiners. The crosses L4 x T2 (1581.69g), L5 x T4 (1365.00g), L6 x T4 (1359.65g) and L2 x T4 (1224.48g) have been identified as good specific combiners for fruit yield per vine. The best performing parents can be used for further breeding programmes and hybrids could be exploited for cultivation.